Hygge: Rahasia Hidup Bahagia Orang Denmark - Frendi Krisman Gulo (Literaksi: Jurnal Manajemen Pendidikan, 2023)
The purpose of this study is to find out a brief study of the thoughts from the Youtube channel M Channel entitled "Hygge: The Secret of a Happy Life of Danish People". In this study, researchers used a qualitative approach with the note-taking method because of the source of data obtained by the author through listening. The result of a brief review of the listening process of this Youtube channel is that Hygee reflects the values of Danish society, such as equality and the well-being of all people. This attitude will have a good impact on our lives. It also narrates solutions to the happy style of the Danes.